Arsitektur Kontekstual Sebagai Tema Rancangan Desain Sanggar Seni Tari Ramah Disabilitas Di Gianyar, Bali: bahasa indonesia - Ni Kadek Ari Manik Lukita; I Putu Hartawan; A.A. Gede Raka (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
The theme is an idea that underlies the design and is translated into the design concept. The theme of a work will give character or impression to the final design, and as much as possible give a message or make the building able to communicate with its environment. Based on the goal to be achieved, which is to provide comfort for design users, especially persons with disabilities, hereby the determination of contextual themes is a classification of contextual areas in architecture related to the environment, surrounding conditions, society, culture. The method presented in planning design proposals is a qualitative analysis method obtained through direct surveys using literature study data and field work with observations and interviews with informants. The results obtained were in the form of data on the number of people with disabilities in Gianyar Regency, data on community interest in dance in Gianyar Regency, and data on the strategic location of design proposals.